THE EXTENSION OF GEOGRAPHICAL INDICATION PROTECTION: NECESSARY FOR DEVELOPING COUNTRY - Mas Rahmah (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2014)
This paper analyses the need of extension of Geographical Indication (GI) protection since the current protection under Trade Related Aspect of Intellectual Property Rights (TRIPS) is insufficient to cover all products as a result of discriminatory provisions in TRIPS regulating a greater protection to wines and spirits only and different level of GI protection under Article 22 and Article 23 TRIPS. This paper then assumes that the extensive GI protection for all products should be supported because it would give greater benefits particularly to developing countries such as prevent the free riding, attract regional investment and obtain market power. Perlindungan Indikasi Geografis (IG) perlu diperluas tidak hanya pada produk tertentu seperti wines danspiritskarena perlindungan IG diatur di dalam TRIPS tidak cukup memberikan perlindungan kepada semua produk sebagai akibat perbedaan pengaturan di TRIPS yang memberikan perlindungan lebih kepada wines danspirits saja dan adanya perbedaan tingkat perlindungan pada Pasal 22 dan 23 TRIPS. Perluasan perlindungan IG harus didukung karena akan memberikan manfaat khususnya kepada negara berkembang. Perluasan perlindungan IG dapat melarang pemboncengan reputasi, menarik investasi dan meningkatkan kekuatan produk negara berkembang di pasaran.